The transmission dynamics of the monkeypox virus in the presence of environmental transmission - Madubueze, Chinwendu E.; Onwubuya, Isaac O.; Nkem, Godwin N.; Chazuka, Z. (Frontiers in Applied Mathematics and Statistics, 2022)
A deterministic model for the environmental transmission dynamics of monkeypox with the presence of quarantine and vaccination is presented. The analysis of the model presented three important equilibrium states namely; monkeypox-free equilibrium (MPXV-FE), infected rodent-free endemic equilibrium (IRF-EE) and Coexistence equilibrium (CO-EE). The local and global stability of the equilibrium states is established in terms of reproduction numbers. For global stability, the Comparison theory is used for MPXV-FE while the Voltera-Lyapunov matrix theory is used for both IRF-EE and CO-EE. Sensitivity analysis is performed using the Latin Hypercube sampling method with the results showing that environmental transmission parameters are the main driver of infection in the dynamics of monkeypox infection. This is further supported by numerical simulations to show the impact of environmental transmission on monkeypox infection and also the validity of the theoretical analysis presented. Based on the results, it is recommended that health practitioners and policy-makers should constitute control strategies that will focus on reducing environmental transmission and shedding of the virus in the environment while increasing the environmental decay rate of the monkeypox virus. This will complement the quarantine and vaccination strategies in place.